Arranged marriages in multilateral partnerships: Investigating sustainable human development financing of belize in the World Bank group. A brand relationship theory approach - Jacqueline D. Ifield; Chia-Han Yang (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The structure of multilateral financial partnerships has many relationship challenges, which need to be solved to positively impact sustainable human development. There is a lack of understanding in the development relationship between the so-called developed and developing countries, and development economics theories and research, which guide policies, knowledge, and funding to nations in need. Amid widespread pleas for change to the structure, Belize is a country, which remains in an economic development crisis 41 years after joining the World Bank Group. This original paper, uniquely positions "World Bank" as a brand, and adds to missing empirical research on Belize and development economics with a mixed-methods, brand relationship approach. The researchers perform a survey of 20 years of Belize government personnel dialogues about the Bank, and apply Fournier's (1998) brand relationship theories as tools to measure their perceptions of the Bank as well as get a deeper understanding of the relationship. This investigative research finds that Belize perceives it has an "arranged marriage" type brand relationship with the Bank: it is not a sustainable development partner. This brand relationship also negatively affects the way government personnel see themselves and their abilities. The World Bank Group must innovate its development economics methods and practices, assert its social mission, and meet the development needs of its members by first building genuine brand bonds with them. Debtor member countries must re-define their worth, join together, and design their own paths to sustainable development. All countries are developing.
Keywords: 650; Belize; brand; branding; development economics; human development; knowledge economy; multilateral framework; sustainable development; World Bank